Beyond-CMOS nanodevices 2 - Balestra, Francis (London : ISTE ; Hoboken, NJ : Wiley, 2014)
This book offers a comprehensive review of the state-of-the-art in innovative Beyond-CMOS nanodevices for developing novel functionalities, logic and memories dedicated to researchers, engineers and students. The book will particularly focus on the interest of nanostructures and nanodevices (nanowires, small slope switches, 2D layers, nanostructured materials, etc.) for advanced More than Moore (RF-nanosensors-energy harvesters, on-chip electronic cooling, etc.) and Beyond-CMOS logic and memories applications.
Chapter 4. Nanoelectromechanical Switches4.1. Context; 4.2. Nanorelay principles; 4.2.1. The electrostatic actuation; 4.2.2. The piezoelectrical actuation; 4.2.3. The magnetic actuation; 4.2.4. The thermal actuation; 4.3. Electrostatic nanorelay modeling and optimization; 4.3.1. Dynamic modeling; 4.3.2. Quasi-static modeling; 4.4. Technological challenges for NEMS computing; 4.4.1. Low voltage operation; 4.4.2. Reliability of contact technology; 4.5. NEMS-based architectures; 4.5.1. Conventional architectures; 4.5.2. Adiabatic architectures; 4.6. Conclusions; 4.7. Bibliography.
Description based on print version record.
Keywords: Nanoelectronics; Nanostructures; Metal oxide semiconductors, Complementary; TECHNOLOGY & ENGINEERING / Mechanical; Metal oxide semiconductors, Complementary; Nanoelectronics; Nanostructures; Electronic books; Electronic books